Comparative study of language learning strategies used by first-year students at Prince of Songkla University, Pattani Campus, Thailand and UniMAP, Malaysia - Rongdara, Rochanahasadin (Universiti Malaysia Perlis (UniMAP), 2020)
Link to publisher's homepage at https://jcsi.unimap.edu.my/